Análise da erosão interna de solos em barragens com base na distribuição de vazios - Marcos de Avila Pimenta Filho (2013)
Internal erosion, along with overtopping events, are the main causes of dam failures in the world. This phenomenon occurs when particles of a base soil undergo excessive washing through due to embankment's seepage because of absence or poor performance of the filter system. The problem of filtering, either related to the design or performance evaluation, is generally discussed in terms of the characteristic diameters of base soil and filter materials. Although the criteria usually applied to the design of filters are considered satisfactory, they are based on results of laboratory tests and do not have a theoretical basis for assessing washing through, or for determining the distance that a base soil particle can migrate through the filter constrictions. In this context, Professor Araken Silveira (Silveira, 1964), in order to establish design criteria - not just in terms of particle sizes, but also in order to determine the thicknesses of filters - developed a theory for determining the constriction size distribution of materials, from which it is possible to simulate washing through phenomenon. This geometric-probabilistic methodology allows to determine the distances traveled by the particles of the base soil, through the filter, until they find a constriction which restricts its transport. This case study presents an evaluation of the internal erosion process occurred in Balderhead Dam, located in England, in the 60s. Based on the analysis performed, it was found that a considerable portion of particles of the dam core would be subjected to washing through extents larger than the filter thickness, which indicates reasonable agreement with the incident observed at the dam. In addition, it was evaluated the correlation between the obtained results in washing through analysis and the retention ratio D15/d85 - "Classical Terzaghi's Retention Criterion" - which indicated the consistency of this criterion, as previously expected.